Stronger Legs and Lower Body - Bishop, Tim, 1964- (Champaign, IL Human Kinetics, 2012)
Stronger Legs & Lower Body offers the most effective strength training exercises and programs for increasing strength, size, power, and definition in lower-body muscle groups. With 15 training routines and more than 80 exercises ranging from stabilization to Olympic movements, the guide includes ready-to-use programs for every goal.
Include Appendix and Illustration
Keywords: Weight training -- Buttocks exercises -- Exercise